Global miRNA and mRNA expression profiles identify miRNA‐26a‐2‐3p‐dependent repression of IFN signature in systemic sclerosis human monocytes. Issue 7 (4th March 2020) - Ciechomska, Marzena; Wojtas, Bartosz; Swacha, Monika; Olesinska, Marzena; Benes, Vladimir; Maslinski, Wlodzimierz
Abstract: Dysregulation in type I IFN and IFN‐stimulated genes (ISGs) induced by monocytes is one of the key features of systemic sclerosis (SSc) pathogenesis. Abnormalities in microRNA (miRNA) expression are related to excessive IFN production, however the role of miRNA remains largely elusive in SSc monocytes. This study explores global miRNA‐mRNA profiling of SSc monocytes and functional attenuation of IFN and ISGs by specific miRNAs. Global sequencing of mRNA (mRNA‐seq) and miRNA (miRNA‐seq) samples were performed simultaneously on healthy controls and SSc monocytes. Following computational analysis, selected miRNAs–mRNA candidates were validated, correlated with clinical parameters, and tested by functional assays. Transcriptomics data and qPCR analysis confirmed IFN signature in SSc but not in rheumatoid arthritis monocytes. Based on miRNA‐seq analysis, five miRNAs were selected for further validation. Only the expression patterns of miRNA‐26a‐2‐3p and miRNA‐485‐3p were confirmed and negatively correlated with clinical parameters. Exogenous delivery of miRNA‐26a‐2‐3p to TLR‐stimulated monocytic THP‐1 cells specifically inhibited ISGs but not inflammasome activity in functional assays. In conclusion, our miRNA–mRNA co‐sequencing and functional analysis identify miRNA‐26a‐2‐3p as a new candidate, which is predicated to negatively regulate ISGs. This implies that reduced expression of miRNA‐26a‐2‐3 may be involved in pathogenic IFN signature in SSc monocytes. Abstract : Global miRNA–mRNA co‐sequencing analysis has demonstrated that IFN‐stimulated genes (ISG) are increased in SSc monocytes but not in HC and RA monocytes. Selected miRNAs are dysregulated in SSc. Therefore, miRNA‐26a‐2‐3p‐dependent IFN‐blocking strategies can be used as a novel therapy for SSc .